2014
DOI: 10.1104/pp.113.227801
|View full text |Cite
|
Sign up to set email alerts
|

Monoubiquitination of Histone 2B at the Disease Resistance Gene Locus Regulates Its Expression and Impacts Immune Responses in Arabidopsis      

Abstract: Disease resistance (R) genes are key components in plant immunity. Here, we show that Arabidopsis (Arabidopsis thaliana) E3 ubiquitin ligase genes HISTONE MONOUBIQUITINATION1 (HUB1) and HUB2 regulate the expression of R genes SUPPRESSOR OF npr1-1, CONSTITUTIVE1 (SNC1) and RESISTANCE TO PERONOSPORA PARASITICA4. An increase of SNC1 expression induces constitutive immune responses in the bonzai1 (bon1) mutant, and the loss of HUB1 or HUB2 function reduces SNC1 upregulation and suppresses the bon1 autoimmune pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 57 publications
4
92
0
Order By: Relevance
“…SDG8 and SDG25 target genes, CER3 and CCR2, as well as SNC1 were used to determine the impact of H3Kme on H2Bubn. SNC1 is a TIR-NB-LRR-type protein whose gene expression is regulated by H2Bubn (Zou et al, 2014). As expected, the hub1 mutation significantly reduced H2Bubn in SNC1, CCR2, and CER3 promoters and exons ( Figures 9B to 9D).…”
Section: Crosstalk Between Histone Lysine Methylation and H2b Ubiquitsupporting
confidence: 48%
“…SDG8 and SDG25 target genes, CER3 and CCR2, as well as SNC1 were used to determine the impact of H3Kme on H2Bubn. SNC1 is a TIR-NB-LRR-type protein whose gene expression is regulated by H2Bubn (Zou et al, 2014). As expected, the hub1 mutation significantly reduced H2Bubn in SNC1, CCR2, and CER3 promoters and exons ( Figures 9B to 9D).…”
Section: Crosstalk Between Histone Lysine Methylation and H2b Ubiquitsupporting
confidence: 48%
“…H2Bub1 plays critical roles in regulating growth and development (Fleury et al ; Liu et al ; Cao et al ; Gu et al ; Schmitz et al ; Xu et al ; Bourbousse et al ; Himanen et al ; Cao et al ), as well as in modulating defence or immune responses and in cuticle composition in plants (Devoto et al ; Dhawan et al ; Hu et al ; Menard et al ; Zou et al ). In the present study, we demonstrated that H2Bub1 played an important role in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H2Bub1 has been found to play a role in plant defense against pathogens. hub1 mutants show increased susceptibility to the necrotrophic fungal pathogens Botrytis cinerea and Alternaria brassicicola (Dhawan et al, 2009), and HUB1 and HUB2 have been shown to regulate the expression of R genes SUPPRESSOR OF npr1-1, CONSTITUTIVE1 and RESISTANCE TO PERONOSPORA PARASITICA4 via histone monoubiquitination at the R gene locus (Zou et al, 2014). Further, H2Bub1 mediated by HUB1/HUB2 is also involved in regulating the dynamics of microtubules to alter the defense response to Verticillium dahliae toxins in Arabidopsis (Hu et al, 2014).…”
mentioning
confidence: 99%